Cerebrospinal Fluid Histamine Levels in Healthy Children and Potential Implication for SIDS: Observational Study in a French Tertiary Care Hospital - Plancoulaine, Sabine; Guyon, Aurore; Inocente, Clara-Odilia; Germe, Philippine; Zhang, Min; Robert, Philippe; Lin, Jian-Sheng; Franco, Patricia (Frontiers in Pediatrics, 2022)
Objective: A defect of the waking systems could constitute a factor of vulnerability for sudden infant death syndrome (SIDS). A decrease in orexin levels, which promotes wakefulness and activates histaminergic neurons (another hypothalamic wake-promoting system) has already been demonstrated between 2 and 6 months. This work aims to study the levels of histamine (HA), tele-methylhistamine (t-MeHA), its direct metabolite, and t-MeHA/HA ratio in the cerebrospinal fluid (CSF) of healthy children, to evaluate the maturation of the histaminergic system and its possible involvement in SIDS. Methods: 78 French children between 0 and 20 years (48.7% boys) were included, all of whom had a clinical indication for lumbar puncture, but subsequently found to be normal. Measurements of HA and t-MeHA in CSF were performed by reverse phase liquid chromatography coupled to mass spectrometry detection. Statistical analyses were performed using Spearman correlations and non-parametric pairwise ranking tests. Results: A negative correlation was found between age and CSF HA (r = -0.44, p<10-4) and t-MeHA (r = -0.70, p<10-4) levels. In pairwise comparisons, no difference in CSF HA and t-MeHA levels was observed between youngest age groups (i.e., 0-2 mo vs. 3-6 mo), but CSF HA and t-MeHA levels were significantly lower in older children (i.e., > 6 mo vs. 0-6 mo). The CSF HA decrease with age was only observed in boys, who also presented global lower CSF HA levels than girls. Conclusion: CSF HA and t-MeHA levels decrease with age in boys, and global levels are lower in boys than in girls. These results reveal changes in histaminergic transmission and metabolism during maturation. Whether lower CSF histamine values in boys compared to girls could contribute to their higher risk of SIDS warrants further research.